2014
DOI: 10.1101/gad.232058.113
|View full text |Cite
|
Sign up to set email alerts
|

The Gpr1/Zdbf2 locus provides new paradigms for transient and dynamic genomic imprinting in mammals

Abstract: Many loci maintain parent-of-origin DNA methylation only briefly after fertilization during mammalian development: Whether this form of transient genomic imprinting can impact the early embryonic transcriptome or even have life-long consequences on genome regulation and possibly phenotypes is currently unknown. Here, we report a maternal germline differentially methylated region (DMR) at the mouse Gpr1/Zdbf2 (DBF-type zinc finger-containing protein 2) locus, which controls the paternal-specific expression of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
67
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(70 citation statements)
references
References 61 publications
1
67
0
2
Order By: Relevance
“…To date all imprinted domains contain at least one differentially methylated region (DMR) that acquires methylation during gametogenesis (germline DMR, or gDMR), and maintained throughout development. Some imprinted loci also contain DMRs that become allelically methylated in the embryonic diploid genome (somatic DMRs, or sDMR) which are under the hierarchical influence of gDMRs [4, 9, 10]. Recently, transiently methylated germline DMRs (tDMRs) have been identified in mice that are indistinguishable from ubiquitous imprinted gDMRs in gametes and preimplantation embryos [11].…”
Section: Introductionmentioning
confidence: 99%
“…To date all imprinted domains contain at least one differentially methylated region (DMR) that acquires methylation during gametogenesis (germline DMR, or gDMR), and maintained throughout development. Some imprinted loci also contain DMRs that become allelically methylated in the embryonic diploid genome (somatic DMRs, or sDMR) which are under the hierarchical influence of gDMRs [4, 9, 10]. Recently, transiently methylated germline DMRs (tDMRs) have been identified in mice that are indistinguishable from ubiquitous imprinted gDMRs in gametes and preimplantation embryos [11].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, transient imprinting and aberrant allele switching have been implicated in developmental and disease-related phenotypes [16,17]. For example, during mammalian development, many loci maintain parent-of-origin DNA methylation only briefly after fertilization [16]. Antisense noncoding RNA has also been implicated in the imprint switch mechanism in breast cancers [17].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, by separating male and female blastocysts using an X egfp transgenic strain, we demonstrated that Plac1 gene is paternally expressed before implantation and then switched to be maternally expressed after implantation. Recently, transient imprinting and aberrant allele switching have been implicated in developmental and disease-related phenotypes [16,17]. For example, during mammalian development, many loci maintain parent-of-origin DNA methylation only briefly after fertilization [16].…”
Section: Discussionmentioning
confidence: 99%
“…ZDBF2 is a unique imprinted gene in that it contains both maternal and paternal marks (Duffie et al 2014). During the pre-implantation period and in the placenta after implantation, the maternal allele is silenced.…”
Section: Discussionmentioning
confidence: 99%